Clinical measures of obesity and cumulative cardiometabolic risk in adolescents. (27th December 2016) - Jayawardene, W. P.; Lohrmann, D.; Dickinson, S.; Talagala, S.; Torabi, M.
Summary: Obesity tracks from childhood to adulthood most strongly of all cardiometabolic risk factors. To determine relationship of body mass index (BMI) and waist circumference (WC) with cardiometabolic risk (dyslipidemia, hyperglycemia and elevated blood pressure) in a large U.S. population ages 12–19 and demographic subgroups. Pooled 1999–2014 National Health and Nutrition Examination Survey data were analyzed ( N  = 23 438). In addition to standard cutoffs of BMI and WC, risk levels were identified for each laboratory variable: HDL‐cholesterol, LDL‐cholesterol, triglycerides, total cholesterol (category = lipids); fasting glucose, glycated haemoglobin (category = glucose); systolic/diastolic pressures (category =blood pressure). Within each category, being high‐risk on any of the variables was high‐risk; being borderline‐risk on any, without being high‐risk on any, was borderline‐risk. Obesity severity was strongly associated with increased cardiometabolic risk, with prevalence of borderline‐risk greater than high‐risk. Anthropometric indicators in males and Hispanics, versus females and Whites/Blacks, respectively, had stronger associations with cardiometabolic risks. BMI and WC performed well for identifying adolescents with at least one borderline‐risk or high‐risk level measure for lipids, glucose and blood pressure; relationship strength varying by gender and race/ethnicity. Thus, to prevent or better manage clinical diseases of adolescents with elevated BMI and/or WC, all recommended laboratory tests are warranted.